THE CURRENT COMPATIBILITY OF MODERN PEDAGOGY WITH NATIONAL EDUCATION - Rаkhmonovа Sаodаt Orzu kizi (Modern American Journals, 2025)
The article discusses the issue of harmony between modern pedagogy and the national education system. In the current era of globalization, the need to use not only advanced technologies and modern methods in educating the younger generation, but also to instill national values is substantiated. The article analyzes the basic principles of national education, approaches to modern pedagogy and ways to ensure harmony between them. Also, the practical results of this harmony are shown on the example of positive experiences in Uzbekistan.
Keywords: National values, modern pedagogy, education, harmony, innovative methods, competency-based education, education of the younger generation, teacher-student tradition.